2011
DOI: 10.1889/1.3621034
|View full text |Cite
|
Sign up to set email alerts
|

P‐20: Highly Stable Amorphous Indium Gallium Zinc Oxide Thin‐Film Transistors with N2O Plasma Treatment

Abstract: Amorphous InGaZnO 4 (a-IGZO) thin film transistors (TFTs) are promising devices in backplane technology. Since a-IGZO TFTs are very sensitive to the fabrication processes, they need stable process to keep their initial deposition properties. Herein we improved the stability of a-IGZO by applying N 2 O plasma. The stability characteristic of a-IGZO TFT was improved with N 2 O plasma. V th shift was 1.5V for 10,000s under NBTS with illumination which was the best result in the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…It is shown that devices with N O treatment have better electrical stability than devices with O treatment during the DC stress. The stress result is quite consist with previous report that devices with N O treatment have better electrical stability [24]- [26] owing to the effect of repairing of device back channel defect [27], [28].…”
Section: Device Fabricationsupporting
confidence: 88%
“…It is shown that devices with N O treatment have better electrical stability than devices with O treatment during the DC stress. The stress result is quite consist with previous report that devices with N O treatment have better electrical stability [24]- [26] owing to the effect of repairing of device back channel defect [27], [28].…”
Section: Device Fabricationsupporting
confidence: 88%
“…To improve the stability, a few annealing processing steps are added after the deposition of active layer and insulators. The details of fabrication are presented in the reference [4,5].…”
Section: Oxide Tft Manufacturing Processmentioning
confidence: 99%
“…To overcome these problems, oxide TFT backplane technology was suggested in 2004 [2]. Many researchers have found the amorphous In-Ga-Zn-oxide (a-IGZO) as a possible material with higher mobility (~10 cm 2 /Vs) and lower off-current (~ 10 -17 A), along with compatibility to the a-Si process of existing mass production lines [3][4]. Higher mobility renders high resolution and narrow bezels due to the improved charging characteristics for both pixel and integrated gate-drivers.…”
Section: Introductionmentioning
confidence: 99%